Casting light on the European anchovy: from biology to conservation and industry - Mutalipassi, Mirko; D’Anza, Emanuele; Pugliano, Mariagiulia; Firmamento, Roberto; Murano, Carola; Ruocco, Nadia; Pennesi, Chiara; Procaccini, Gabriele; Romeo, Teresa; Terlizzi, Antonio; Peretti, Vincenzo (Frontiers in Ecology and Evolution, 2024)
This manuscript explores the role of European anchovies (Engraulis encrasicolus) in the central Mediterranean Region, shedding light on their ecological significance, conservation challenges, and sustainable utilization. The European anchovy is one of Europe's most important fish resources in the Mediterranean basin, and it is considered a keystone species, playing a pivotal role in both ecological and socio-economic dimensions. However, in recent decades, European anchovy, together with Sardina pilchardus (commonly known as European sardine), has suffered a population decline for several reasons. Consequently, it is necessary to improve the management of anchovy fisheries by understanding the reproductive modes and characteristics, the influence of currents on the passive transport of eggs and larvae, the feeding habits, the environmental adaptability (e.g., salinity), and the distribution of ecotypes along the Italian coasts. Such information is fundamental for the management of fisheries, especially artisanal ones, and to control frauds, especially in protected, geographically referred, and traditional highquality commercial products. Various aspects, ranging from their population dynamics to their industrial processing and the ecological implications of these activities were delved, highlighting the knowledge about anchovy populations and ecotypes and its importance in maintaining ecosystem balance and sustaining human communities. The ecological interaction of anchovies within the food web, as essential data in the conservation actions and management of these resources was emphasized. In addition, the metabolic and stomach contents diversity among anchovy populations and ecotypes was discussed, enhancing our understanding of their adaptability to varying environmental conditions. The manuscript then explores the traditional and industrial processing of anchovies, encompassing aspects ranging from fishing techniques (i.e., methods of capture) to their industrial significance, sustainability concerns, issues of fraud, and the establishment of geographical traceability. Finally, the opportunities for sustainable and biotechnological utilization of anchovy discards were also further explored, demonstrating the potential for waste reduction and resource optimization.